Palliative Care in Resource-poor Settings: Inequalities, Challenges, and Opportunities - Dangal, Ganesh; Paudel, Bishnu Datta; Jha, Anjani Kumar (Journal of Nepal Health Research Council, 2018)
Palliative care is, according to WHO,â€œan approach that improves the quality of life of patients and their families facing the problems associated with life-threatening illness, through the prevention and relief of sufferingâ€. The need for palliative care is increasing throughout the world as it is well known that palliative care improves quality of life for seriously ill patients and their families but the palliative care needs of all patients are being addressed inadequately in resource-poor settings. Although developed western world has a rapidly growing system in place for palliative care services, clinical, research and educational programs; it is negligible in the developing countries.